2021
DOI: 10.1088/1361-6528/ac3617
|View full text |Cite
|
Sign up to set email alerts
|

Droplet epitaxy of InAs/InP quantum dots via MOVPE by using an InGaAs interlayer

Abstract: InAs quantum dots (QDs) are grown on an In0.53Ga0.47As interlayer and embedded in an InP(100) matrix. They are fabricated via droplet epitaxy (DE) in a metal organic vapor phase epitaxy (MOVPE) reactor. Formation of metallic indium droplets on the In0.53Ga0.47As lattice-matched layer and their crystallization into QDs is demonstrated for the first time in MOVPE. The presence of the In0.53Ga0.47As layer prevents the formation of an unintentional non-stoichiometric 2D layer underneath and around the QDs, via sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 36 publications
(66 reference statements)
4
15
0
Order By: Relevance
“…We studied many topographic images, and we conclude that the local drilling effect is absent in all the DEQDs in sample B. From the 200 nm long image shown in Figure a, it is evident that the long-range-etching effect shown in Figure b is also suppressed, as expected from previous AFM and TEM investigations . Yoon et al suggested that this is a result of the change in the growth kinetics from the mass-transport regime on InP to the surface-reaction-limited regime on InGaAs.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…We studied many topographic images, and we conclude that the local drilling effect is absent in all the DEQDs in sample B. From the 200 nm long image shown in Figure a, it is evident that the long-range-etching effect shown in Figure b is also suppressed, as expected from previous AFM and TEM investigations . Yoon et al suggested that this is a result of the change in the growth kinetics from the mass-transport regime on InP to the surface-reaction-limited regime on InGaAs.…”
Section: Resultssupporting
confidence: 73%
“… 22 Here, we discuss the mechanism of such trench formation for the first time with atomic resolution. We show that both etching processes can be suppressed by growing a thin InGaAs interlayer prior to the droplet deposition as suggested by Sala et al 35 QDs crystallized at 520 °C have lower size inhomogeneity compared to QDs crystallized at 480 °C. We note that, in our previous work, 34 the indium droplets were formed at 400 °C and the crystallization temperature was up to 500 °C.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations